1996
DOI: 10.1046/j.1526-4610.1996.3601053.x
|View full text |Cite
|
Sign up to set email alerts
|

Meningeal Hyperperfusion Visualized by MRI in a Patient With Visual Hallucinations and Migraine

Abstract: A 41-year-old patient with a history of migraine but with no history of seizures had intermittent prolonged and variable complex visual hallucinations and illusions lasting 9 days, accompanied by unilateral headache. Electroencephalography during these visual symptoms revealed occipital epileptic discharges. Distinction between focal migrainous attacks and ictal phenomena was difficult. Magnetic resonance imaging showed a lesion in the right visual cortex probably related to low perfusion and hyperemia of meni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 9 publications
2
13
1
Order By: Relevance
“…In somepatients with migraine with aura delayed hyperemia has been observed and it often persists longer than the headache (5). Lindner et al reported a patient who had visual hallucinations and headache and the MRIscan revealed hyperintense meningeal signal over the right visual cortex (6). They suggested that this finding was due to primary parenchymal hyperperfusion in the course of a classic migraine attack and that the MRImay be helpful in differentiating between migraine and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In somepatients with migraine with aura delayed hyperemia has been observed and it often persists longer than the headache (5). Lindner et al reported a patient who had visual hallucinations and headache and the MRIscan revealed hyperintense meningeal signal over the right visual cortex (6). They suggested that this finding was due to primary parenchymal hyperperfusion in the course of a classic migraine attack and that the MRImay be helpful in differentiating between migraine and epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in migraine without aura no changes in cerebral blood flow were observed during spontaneous migraine or that evoked by angiography (Olesen et al, 1981). In contrast to cerebral blood flow measurements, few studies have investigated flow within the meninges, although one notable exception is one case study showing a hyperemia in the meninges measured using magnetic resonance imaging in a patient suffering migraine with aura (Lindner et al, 1996).…”
Section: Evidence For Vasodilation During Migrainementioning
confidence: 98%
“…[10][11][12] We believe that alteration of the BBB, which may cause hyperperfusion, may be the main mechanism for our patient's particular cerebral edema. From the acute to subacute phase, it presumably represents vasogenic edema resulting from alteration of the BBB.…”
Section: Discussionmentioning
confidence: 83%